Numerical evaluation of the side wall effect on the flow around a hydrofoil. Issue 3 (2014) - Min He; Lingli Yuan; Lingjiu Zhou; Jing Yang; Zhengwei Wang
<x xml:space="preserve"> Abstract </x> Purpose – Studies of the three‐dimensional flow characteristics during hydrofoil cavitation have shown that the side walls strongly affect the flow field around the hydrofoil. The purpose of this paper is to analyze the side wall effect for three‐dimensional non‐cavitating flows around a hydrofoil. Design/methodology/approach – A three‐dimensional non‐cavitating flow field around a hydrofoil is analyzed for different attack angles using the RNG turbulence model and large eddy simulations (LES). The effect of the hydrofoil span was analyzed using LES simulations for various spans. Findings – The lift coefficient, drag coefficient and pressure coefficient on the suction side are compared with experimental values. The results from the LES model (Smagorinsky‐Lilly subgrid‐scale model) agree better with the experimental data than those from the RNG turbulence model. Originality/value – This paper shows that the flow around the hydrofoil has significant three‐dimensional characteristics due to the side wall. For wide hydrofoils, the wall vortex region becomes essentially stable, and the width of the span has little effect on the middle region. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors gratefully acknowledge the support from the National Natural Science Foundation of China (No. 50879088). </ack>